2019
DOI: 10.1177/2055102919844504
|View full text |Cite
|
Sign up to set email alerts
|

Illness perception and high readmission health outcomes

Abstract: This review identified associations between illness perception and health outcomes of patients with a medical diagnosis included in the Hospital Readmissions Reduction Program. Inclusion criteria were English language, use of quantitative methodology, health outcomes specified, and identifiable effect size and statistical significance of the relationship. Most of the 31 studies in this review showed that favorable illness perception has been associated with better health outcomes, while unfavorable illness per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 55 publications
6
53
0
10
Order By: Relevance
“…Finally, we compared the overall study population with a larger cohort of Hispanic/Latino adults with T2D cohort published previously. 30 We confirmed various biological similarities as well as indication of various psychosocial similarities between the two samples.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Finally, we compared the overall study population with a larger cohort of Hispanic/Latino adults with T2D cohort published previously. 30 We confirmed various biological similarities as well as indication of various psychosocial similarities between the two samples.…”
Section: Discussionsupporting
confidence: 72%
“…Perceptions of the meaning of disease are influential in health outcomes, with favorable illness perception associated with better health outcomes, and unfavorable perception associated with worse outcomes. 29,30 To explore this possibility, we went beyond biological descriptors and quantitative psychosocial metrics (e.g., achieved HbA 1c , weight, insulin use, and depression) to explore qualitative perceptions of diabetes. Specifically, two independent bilingual raters conducted thematic analysis of answers to the question, ''In your own words, what is diabetes?''…”
Section: Participant Activitiesmentioning
confidence: 99%
“…This finding implies that providing accurate, concise, and up-to-date information regarding the transmission, mechanism, symptom severity, and plausible treatment of COVID-19 can help increase public awareness of the hazards and risks of harm from COVID-19. Illness perception, which refers to the cognitive appraisal and personal understanding by people of a novel infectious disease [ 14 ], can largely influence not only their psychological and behavioral responses to the illness condition, but also their health outcomes [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who perceived their disease activity had worsened were more likely to use healthcare services.Meanwhile, patients who perceived their disease activity had improved were more likely to delay their visits. Many researchers have suggested that patient's behavior in healthcare-seeking is driven by perception of illness experience (eg, symptoms, diagnosis, and severity),42,43 which might be triggered by physiological or psychological etiologies 44. However, the fact of the matter is that increased demand for healthcare services during the current pandemic could subsequently threaten to overwhelm the healthcare system.Our findings also demonstrated a significant negative correlation between a patient's perception of disease activity and medication adherence.…”
mentioning
confidence: 99%